Spiritual Leadership, Organizational Culture, and Self-Efficacy as Predictors of Lecturer Performance in Indonesian Higher Education: A PLS-SEM Analysis in Probolinggo - Abd Aziz; Poppy Rachman; Juliansyah, Juliansyah; Murfi, Ali (Jurnal Pendidikan Islam, 2024)
Purpose – In response to the challenges posed by the Fourth Industrial Revolution, enhancing lecturer competitiveness has become crucial to ensuring the sustainability of higher education quality in Indonesia. This study aims to empirically examine the influence of spiritual leadership, organizational culture, and self-efficacy on lecturer performance, with a particular focus on higher education institutions in Probolinggo Regency, East Java—an area previously underexplored in academic research. Design/methods/approach – This study employs a quantitative correlational approach involving 220 lecturers from ten higher education institutions in Probolinggo. Data were collected through a closed-ended Likert-scale questionnaire and analyzed using SmartPLS 4.0 through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to assess the causal relationships among latent variables. Findings – The analysis reveals that all three independent variables—spiritual leadership (β = 1.330; p < 0.001), organizational culture (β = 1.588; p < 0.001), and self-efficacy (β = 0.503; p < 0.001)—have a significant impact on lecturer performance. The model demonstrates an R² value of 0.598, indicating that 59.8% of the variability in lecturer performance can be explained jointly by these three factors. Research implications – The findings have direct implications for higher education human resource development policies, particularly in fostering value-based leadership, strengthening adaptive work culture, and enhancing lecturers’ psychological capacity to promote sustainable academic performance.